OS6 - 210 Gliomas in Young Adults: Presence of Mutations in Histone Genes. (18th October 2016) - Munoz, D. G.; Ryall, S.; Das, S.; Hawkins, C.
Abstract : A point mutation resulting in a specific amino acid change(K27M) in either one of the genes encoding histone H3, H3F3A (H3.3) or HIST1H3B/C/I (H3.1)is present in most pediatric intrinsic pontine gliomas, and has been described in other midline locations. The objective of the present study was to determine the frequency and location of this mutation in diffuse infiltrating gliomas in young adults. The study group consisted of 22 consecutive diffuse gliomas in patients under the age of 40 treated at St. Michael's Hospital, an adult hospital in the University of Toronto system. Ultra-sensitive digital droplet PCR, a method capable of highly sensitive and specific mutation detection affecting either H3.3 or H3.1, was performed on sample DNA to determine H3K27M status. The H3K27M mutation was detected in the gliomas of five patients, aged 17 to 34 years. The male: female ratio was 3:2. The allele frequency ranged from 26% to 44%, reflecting the infiltrating character of the tumors. Three of the tumors where located in the thalamus, one in the medulla, and one was intraventricular. In terms of grading, one tumor was considered WHO grade II, two III, and two IV. In contrast, most tumors in patients with gliomas lacking the K27M mutation (17 subjects, age 19 to 39 years) were located in the lobes of the cerebral hemispheres, with the following exceptions: 1 in the thalamus, 1 in the hypothalamus, 1 in the cerebellum, and 1 periventricular. WHO grades were 1 II, 9 III, 7 IV. Correlation with patient outcome is ongoing. We conclude that the H3K27M is common in thalamic gliomas in young adult patients, and rare or absent in lobar hemispheric gliomas.